Agro-food manufacturing in Mediterranean Spanish regions: Andalusia versus Valencian region - Daniel Coq Huelva (European Regional Science Association (ERSA), 2003)
Agro - food manufacturing is a basic activity in economic structure of Mediterranean regions. Spanish Mediterranean regions are not an exception in this pattern of specialization. Agro - food manufacturing is very important in all the Spanish Mediterranean regions (Catalonia, Valencia, murcia and Andalusia). But there are some problems of reduced articulation of economic activities in southern Spanish Mediterranean regions that are not perceived in other Mediterranean spaces (Catalonia or Valencia). The aim of this article is to compare the different patterns of behavior of agro - food manufacturing in two different Spanish Mediterranean regions: Andalusia and the Valencia community. Andalusia is a region that represents approximately 18% of Spanish population and territory. However, his participation in national g.d.p. is only of 12%. So, Andalusia is a region with some degree of backwardness in Spanish context. One of the rare activities where Andalusia has a participation of national average higher than his participation in population is agro food manufacturing. Andalusian agro food manufacturing represents 25% of total Spanish value added. Valencian community however is a richer regions and it has a more diversified manufacturing structure. The comparing between the two regions will allow to evaluate if the patterns of relation of agro - food manufacturing with the rest of regional economic activities are similar in both region or there are important changes between them. This fact is very important for the design of a regional economic policy. Traditionally, the thesis of lack of economic articulation and orientation of economic activities toward other spaces has been defended in southern regions, especially in Andalusia. From this point of view, these elements decreased the possibilities of actuation of regional policies. However, agro - food manufacturing, even in regions like Andalusia did not experience this kind of problems. In 1980 more of the 80% of the inputs used by this industry had regional origins. But in 1995 this participation was of the 63,3%. So there is a process of substitution of regional inputs for non-regional inputs even in activities with traditionally strong ties with regional productive structure, like agro - food manufacturing. In this text, this hypothesis will be tested, comparing Andalusian situation with other regional situations a priori non-affected by this problem, like Valencian region. Input - output tables of Andalusia and Valencian region will be employed to analyze this fact. The analysis will be carried for the agro - food manufacturing and for different sectors included inside. It will be possible so to study with a relative high degree of detail the reality of agro - food manufacturing in two concrete regions that, possibly, are representatives of a more general dynamic.
Keywords: 330